Study of Nozogeographic Situation and Its Study on the Basis of Sociological Survey - Nilufar Kh. Komilova1 , Lolakhon K. Karshibaeva2 , Umriniso T. Egamberdiyeva3 , Zulfiya L. Abduvalie (Institute of Medico-legal Publications Pvt Ltd, 2020)
Development of scientific and practical recommendations on improvement of nosogeographic situation by assessing the impact of nosogeographic situation on the territorial structure of diseases and pathological processes of population in Samarkand and Navoi regions. This includes an analysis of the pathological processes associated with the disease of the population of Samarkand, Navoi regions and their districts; Identification and evaluation of natural, socio-economic geographical factors and nosogeographic situation affecting the health of the population in the regions; medical geographical analysis of some infectious diseases occurring among the population of the regions and their specificity; Determine the main problems in the nosogeographical condition of the regions, the prognosis of the existing diseases among the population. The study identified groups and types of diseases that occur in the regions of the region such as Khatirchi, Qiziltepa, Bulungur. The nosocomial situation was assessed on the basis of a sociological survey method.